Carvacrol/β-cyclodextrin inclusion complex inhibits cell proliferation and migration of prostate cancer cells - Trindade, Gabriela G.G.; Thrivikraman, Greeshma; Menezes, Paula P.; França, Cristiane M.; Lima, Bruno S.; Carvalho, Yasmim M.B.G.; Souza, Eloísa P.B.S.S.; Duarte, Marcelo C.; Shanmugam, Saravanan; Quintans-Júnior, Lucindo J.; Bezerra, Daniel P.; Bertassoni, Luiz E.; et al. (Food and chemical toxicology, 2019)
Carvacrol, a phenolic monoterpene derived from thyme oil has gained wide interest recently because of its anticancer activities. To improve the solubility of carvacrol, the formation of inclusion complexes with β-cyclodextrin was performed by ultrasound and freeze-drying methods and characterized using thermal analysis, FTIR, XRD, SEM, NMR and HPLC analysis. From these results, carvacrol was successfully complexed within β-cyclodextrin cavity. Moreover, HPLC analysis demonstrated a higher entrapment efficiency for freeze-drying method (81.20 ± 0.52%) in contrast to ultrasound method (34.02 ± 0.67%). Hence, freeze-drying inclusion complex was evaluated for its antiproliferative effect and cytotoxicity against prostate cancer cell line (PC3) in vitro. Further, freeze-drying complex led to a dose-dependent inhibition in tumor cell growth in 2D and 3D cell culture systems. Altogether, the inclusion of carvacrol in β-cyclodextrin led to the formation of stable complexes with potent antiproliferative effects against PC3 cells, in vitro. Such an improved cytotoxic effect can be attributed to the enhanced the aqueous solubility and bioavailability of carvacrol by effective complexation in β-cyclodextrin. [Display omitted] •CARV/β-CD complexes have been developed to improve the anticancer activity.•The FD method showed high efficiency in the formation of inclusion complexes.•FD complexes enhanced in vitro anticancer activity and cytotoxicity against PC3.•FD complex also reduced the cell viability of PC3 encapsulated in GelMA hydrogels.